Patterns of Chest Injuries among Yemeni Patients: a Retrospective Analysis - Aldahmashi, Mohammed N. (University of Science and Technology, Sana'a, 2015)
Objective: To investigate the patterns of thoracic injuries and the methods used for their management. Methods: A retrospective descriptive analysis of 275 chest trauma cases managed at the University of Science and Technology Hospital over the period 2010-2013. Results: Of 275 consecutive patients with chest trauma, 72.7% were males and 7.27% were females with a mean age of 33.6 years old. Blunt injuries represented 51% (125 males and 15 females) while penetrating injuries represented 49% (130 males and five females) of the cases. Among the penetrating injury group, three patients (1.1%) were with direct sustaining cardiac injuries. The most common presenting features associated with injuries were pain (100%), dyspnea (78.6%) and hemorrhagic shock (17%). Concurrent extrathoracic injuries were found in 22.2% (61/275) of the total chest injuries; spinal cord injuries (3.3%; 9/275), brain injuries (6.2%; 17/275) and intraperitoneal injuries (4.4%; 12/275) and bone fractures (7.3%; 23/275). The first three types of extrathoracic injuries were mostly due to penetrating injuries that necessitated a thoracoabdominal approach or chest tube drainage (CTD) and laparotomy. Computerized tomography scan, chest X-ray, ultrasound and echocardiography were the main diagnostic tools, being used for the diagnosis of 95.27%, 96.72%, 9.73% and 9.33% of cases, respectively. Intercostal tube thoracostomy was required for the management of 96.3% (130/135) of patients with penetrating injuries; early thoracotomy was performed in 25.9% (35/135) of patients to control over bleeding while late thoracotomy was performed in 16.3% (22/135) of patients for removal of retained foreign body and empyema. The CTD was performed in 76.4% (107/140) of patients with blunt injuries, whereas 23.6% (33/140) patients had conservative management and only 2.9% (4/140) of patients underwent thoracotomy. The average hospital length of stay was 6 days for penetrating trauma group and about 7 days for blunt trauma group. Out of all admitted cases, 94.5% (260/275) were cured while 5.5% (15/275) died. Conclusions: It is concluded that CTD is the most appropriate method of treating complicated chest injuries; however, the penetrating trauma has a higher rate of internal damage that requires early intervention to save life, especially for severe or progressive intrathoracic bleeding and cardiac injury. Pulmonary contusion and rib fracture were the most common complications of chest traumas, for which strong painkillers, anti-infective therapy, respiratory care measures and mechanical ventilation are the components of an effective treatment strategy. The associated extrathoracic injuries constitute a major prognostic factor in chest traumas, which were higher in blunt traumas.